Ensimmäinen : Carl Eneas Sjöstrandin istuva Porthan - Siukonen, Jyrki (Suomalaisen Kirjallisuuden Seura, 2023)
The nineteenth century has been called an age of monuments. In some places even one piece made a difference. This book is a study of the intellectual background and physical making of Finland’s first public sculpture, the statue of Professor Henrik Gabriel Porthan by Carl Eneas Sjöstrand. The idealised but sombre Porthan was born under the influence of German neoclassicism. Development on the project was slow but sure. The Swedish artist had to be supported over three years while he was putting together his first monumental piece in Munich and Rome, after which came another three years wait before the cast arrived to Finland. The bronze sculpture, commissioned by the Finnish Literary Society and raised by public subscriptions from people of all classes, was unveiled in the city of Turku in September 1864. Finns took some pride in the fact that, unlike other nations that had raised monuments to kings and generals, here the first place was given to a scholar. In this study Sjöstrand’s pioneering bronze is placed in a wider context and compared with works by his precursors and contemporaries in the international sculptor colony of Rome.
Keywords: historia; veistokset; patsaat; kuvanveisto; muistomerkit; kuvanveistäjät; kulttuurihistoria; julkinen taide; taidehistoria